Analisis Perkembangan Anak Usia Dini Melalui Manajemen Peserta Didik Di TK Pelangi Medan - Agnes Karmelita Daliwu; Dea Sintia Ambarita; Fany Padilah; Fiola Gina Tambunan; Hamidah Hanum Siregar; Nia Devianna Laura Br Tarigan; Elya Siska Angraini (CV. ITTC INDONESIA, 2025)
This study aims to analyze how student management at TK Pelangi Medan supports the optimal development of early childhood. A descriptive qualitative approach was employed, with data collected through in-depth interviews with a class B teacher. The findings reveal that student management is carried out holistically, including an admission process that considers children's readiness, the design of play-based learning activities, and individualized handling of learning challenges through a humanistic approach. Teachers act as facilitators who create enjoyable and adaptive learning environments that meet the needs of children. The main challenges include the diversity of children's characteristics and limited parental involvement. These findings underscore the importance of strong collaboration between teachers and parents, as well as child-centered management strategies, in promoting cognitive, socio-emotional, and motor development in early childhood education.